JURNAL AKUNTANSI & INVESTASI : Kinerja Manajemen Perguruan Tinggi Ditinjau dari Perspektif Pelanggan dan Perspektif Pembelajaran dan Pertumbuhan (Studi Kasus pada Universitas Muhammadiyah Jember) - Nurul Qomariah (Akuntansi FE UMY, 2013)
This study aims to identify and describe the management of the University of Muhammadiyah Jember performance as measured using the Balanced Scorecard approach from the perspective of customers, growth and learning. The population in this study consisted of students, lecturers / professors and employees of the University of Muhammadiyah Jember. Results of the study found that the performance of the University of Muhammadiyah Jember in 2008 as measured by the Balanced Scorecard approach from the perspective of customer total score was 6.6% and from the perspective of growth and learning total score of 13.7%. Thus University of Muhammadiyah Jember in 2008 viewed from the aspect of customers and aspects of growth and learning can be categorized as a company that has a good performance. From these results suggested University of Muhammadiyah Jember should further improve service to students and improve the welfare of its employees.